Technology as an Extension of Personal Capabilities. Reflections for Organizational Development - Miguel Agustín Ortega Carrillo; Diana del Consuelo Caldera González (Technium Social Sciences Journal, 2020)
The present work discusses the importance of the interaction between human beings and technology in the organization. Technology is frequently analyzed at the organizational level from two perspectives. For the Administration, the technology is relevant because it is evident that its use increases production. For Sociology, technology is assumed as a factor that modifies the structure and implies changes in power’s formal distribution. This paper exposes the perspective of organizational development provided with an inherent understanding of the human deeper dimensions. If technology is gaze at as an extension of the capabilities of human beings, then the analysis of the organization is improved with a better understanding of how people interact with technology. Whether technology is seen by people as an enhancer of their own faculties, a competitor who displaces them from their tasks, an active collaborator to achieve objectives, or the achiever of what is simply out of reach of the action of the human being; the study of organizational development need to take account of the interaction between people and technology. The people manifest several degrees of appropriation or rejection of technologies into the organization. Beyond what it is technology, a person attributes it meanings. For the members of an organization, sometimes technology represent a form of dehumanization, although in others it signifies a profound expression of their human dimension. This research is an exploration of these nuances in the organization.